Calculation of coal-water fuel combustion technology based on mathematical modeling - Н.К. Танашева; Л.Л. Миньков; А.Ж. Тлеубергенова; К.К. Саденова (Қарағанды университетінің хабаршысы. Физика сериясы)
Calculation of technology of burning of coal-water fuel (CWF) on the basis of mathematical modeling is presented. Numerical simulation of the process of burning coal-water fuel was carried out in the software package ANSYS Fluent. It is based on the laws of conservation of mass, energy and momentum in a multicomponent medium and the solution of the Navier-Stokes equations, continuity and heat transfer. A mathematical model of the combustion of CWF consists of three phases. For modeling the combustion of pulverized coalwater fuel, using the model of breakup of eddies (Eddy-Dissipation Model) and the parameters of injection of droplets into the furnace were set using the «Discrete Phase Model» function. In ANSYS Fluent, a threedimensional formulation of the problem is given and the Navier-Stokes and Reynolds-averaged energy equations are solved. To account for turbulence, a two-parameter model «k-ε»is chosen.In the course of numerical simulation, the distribution field patterns of velocity vectors were obtained. When conducting a thorough analysis of the furnace temperature regime, we realized that the optimal combustion temperature of CWF is 700–1200 °C. The relation of the particle residence time in the combustion chamber of the furnace on its diameter is obtained.